Your Event Organizer / Oliverra M. Lim ... [et al.] - M. Lim, Oliverra; Quadra, Karmelia Blair; Ahmadi, Mohd Haziq Qusyairi; Ashyreen, Muhammad Farredzul (2015)
Your Event Enterprise is a partnership business between four (4) members; we are Mohd Haziq Qusyairi bin Ahmadi, Karmelia Blair Quadra, Oliverra M. Lim and Muhammad Farredzul Ashyreen bin Asli. Each holds a position General Manager and Marketing Manager, Administration Manager, Financial Manager and Operational Manager respectively. The four of us has agreed in our partnership agreement to each contribute RM16, 500 each as a starting modal for the business which contribute to a total of RM66,000 capitals for this business. "We'll make it happen" is our tagline, which means all those creative ideas of an event from our customers, we will make it happen and make sure they turned up with a huge smile. Our office is located in third floor of Suria Sabah shopping complex here in Kota Kinabalu. Your Event Enterprise is a service based company that organizes events such as Birthdays, Weddings, Grand Dinners and many more event ideas from our customers. However, people might confuse with us being event planners which is who we are. We do not provide all the resources like chairs, lights, tables, canopy and so forth. Our focused is only organizing and by that all the resources are already being supplied. Nevertheless, we do help our customers to find all those resources as well if they needed help with it. We aim for a variety of age from our customers but we mainly focused on the future young generations, who we predict will have an advance idea for an event. We predict that they would have huge imaginations and lots of creative ideas that are unique and different from the now generation. This is why we choose our tagline. We wish to become the most well-known event organizer in Sabah and eventually the whole Asia and for people to not look at us the same as our competitors out there. Not only that, we wish to be able to have more connections out there so that everything that the customer wants we manage to fulfill.